A study on the impact of minimum wage on employees from Mydin company / Fatin Farhana Osman and Norsuriani Basuni - Osman, Fatin Farhana; Basuni, Norsuriani (Faculty of Administrative Science and Policy Studies, 2013)
This research study will focus on the topic of minimum wage in private sector, which is the perception of employee toward the impact of minimum wage. Based on the article of Secretariat, the Minimum Wages Order 2012 which was Gazette on July 16 has to be read together with the National Wages Consultative Council Act 2011 under act 732 (Federal Government Gazette, 2012). The Minister make a recommendation to the government in term of minimum wages rates according to sector, types of employment and regional areas. Thus, the Minister may upon the direction of the Government by notification in the Gazette amend or revoke the minimum wages order.